STRATIGRAPHIC EVIDENCE FOR THE SIBERIA-LAURENTIA CONNECTION AND EARLY CAMBRIAN RIFTING - Pelechaty S.M. (My University, 1996)
Vendian to Cambrian age sedimentary rocks of the northern Siberian craton record Early Cambrian rifting from ˜ 543 to 530 Ma and the onset of regional thermal subsidence in early Tommotian time. A similar tectonic history in the Franklinian basin of northern Canada and Greenland supports the possibility that both basins formed conjugate margins. This correlation constrains both the configuration of the Siberia-Laurentia connection, also supported by paleomagnetic and paleoclimatic data from Siberia, and timing of continental breakup, which is further supported by regional trilobite biostratigraphy. Prior to breakup, Siberia and Laurentia formed a coherent continent that rifted from a western landmass (Australia Antarctica India South China) at ˜ 720 Ma, forming a continuous passive margin along western Siberia-Laurentia. Nearly orthogonal to this margin, the 723 Ma Natkusiak volcanic rocks and Franklin dike swarm in northern Canada are suggested to represent a failed rift that extended into Siberia-Laurentia. Subsequent Early Cambrian separation of Siberia-Laurentia was possibly influenced by crustal heterogeneity created by the failed rift.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская